An Update of Armamentarium for Non Invasive Cardiac Haemodynamics and Congestion Evaluation for Acute Heart Failure Patients - Salvatore Di Somma (Heart Science Journal, 2021)
In the management of Acute Heart Failure(AHF) patients ,current guidelines  suggest  to make a prompt  clinical assessments that include  patient’s congestion and perfusion status evaluation, in order to  start appropriate treatments. Unfortunately ,so far, an accurate evaluation of haemodynamic and fluid status of AHF patients is only possible using invasive methods ;conseguently there is an unmeet need for noninvasive technologies to easly detect  different phenotypes of AHF subjects based on different cardiac haemodynamic profiles . Technological advances such as: Biva,Nexfin or NICas   could  allow for routine noninvasive continuous monitoring of Cardiac Hemodymanics and Fluid content in Acute Heart Failure patients. These  non invasive measurements may provide important information  for improving diagnosis, developing individualized therapeutic management plans/disposition decisions and predicting short term mortality